Causal Therapies in Mucopolysaccharidoses: Enzyme Replacement Therapy - Vartanyan, Ara; Montaño, Adriana M. (Journal of Child Science, 2018)
Enzyme replacement therapy (ERT) for mucopolysaccharidoses (MPS) is the treatment of choice for patients, since it specifically addresses the underlying cause of the disease. Intravenous weekly infusions of recombinant enzymes for MPS I, II, IVA, VI, and VII have proven to be safe and efficacious for somatic symptoms. ERT has been shown to decrease urinary glycosaminoglycan levels and organomegaly, while improving stamina of patients, respiratory function, and quality of life. Although early administration of ERT optimizes outcomes, adult patients still benefit from treatment. ERT has been successfully used as combination therapy with hematopoietic stem cell transplant for patients with MPS I and MPS II, improving patient's cognitive outcomes. Although patients can receive benefit from ERT, current challenges include lack of improvement of neurological manifestations, limited effect on bone disease, development of immune response toward the infused enzyme, and high cost. We will discuss the milestones achieved by intravenous ERT for MPS diseases as well as the current challenges.
Keywords: enzyme replacement therapy; mucopolysaccharidoses; blood–brain barrier; skeletal disease